The Effect of Competence on Employee Performance Mediated on Job Satisfaction (Case Study; Ministry of Finance PPSDM Employee) - Daniel Pangaribuan; Pardomuan Robinson Sihombing (Britain International for Academic Research (BIAR-Publisher), 2021)
Research on competence and its effect on performance and job satisfaction is relatively rare. Included that is still rarely done is research on the effect of competence according to PerMenPANRB Number 38 of 2017 on performance and job satisfaction. This study also analyzes the effect of competence on ASN job satisfaction and places job satisfaction as a mediating variable of competence on ASN performance. Respondents in this study were PPSDM employees of the Ministry of Finance. The results showed that managerial competence had a direct and significant effect on work goals and performance of PPSDM employees. Work objectives have no direct and not significant positive effect on employee performance. In addition, activities do not mediate the effect on employee performance.